What Counts as Equipoise? - Silverman, Henry J. (The Hastings Center report, 2015)
A commentary on “SUPPORT: Risks, Harms, and Equipoise,” by Robert M. Nelson; “The Controversy over SUPPORT Continues and the Hyperbole Increases,” by Alan R. Fleischman; and “SUPPORT and the Ethics of Study Implementation,” by John D. Lantos and Chris Feudtner, all in the January-February 2015 issue.